Formulation and physical stability analysis of red beetroots (Beta vulgaris l.) effervescent granules - Florenly, Florenly; Lokanata, Shieny; Friando, Jovin; Mai, Phuong Thao; Le, Hong Hai; Luzria, Cut Cynthia; Sintapanont, Anusak (Padjadjaran Journal of Dentistry, 2023)
ABSTRACTIntroduction: Red beetroots (Beta vulgaris L.) are a natural ingredient rich in nutrients and provide various notable health benefits. In dentistry, red beetroots have the potential to act as a plaque-disclosing agent. Previous studies showed that red beetroot preparation in gelform is more effective compared to chewable tablets, but has significant drawbacks in taste. Effervescent granules have the potential to conceal the unpleasant taste of beetroot substances. This study aims to determine the ideal formula and evaluate the physical properties and stability of effervescent granules made from red beetroot extract. Methods: This was an experimental design study with descriptive analysis. The maceration method was used to extract the red beetroot constituents. Fresh fruits were collected, air-dried, and macerated with 96% ethanol twice. The filtrates were then concentrated. The wet granulation method was used to formulate effervescent granules. The samples were grouped into formula 1 (F1), formula 2 (F2), and formula 3 (F3) using 1%, 3%, and 4% red beetroot extract, respectively. All sample groups were analyzed for physical stability, namely: organoleptic, flowability, density, dissolving time, and pH tests. Results: All samples surpassed the sensory evaluation for physical properties. Formula 1 (1%) and formula 2 (3%) models passed all the physical stability tests. Meanwhile, the 4% formula (F3) failed two physical tests. F1 (1%) samples also showed lighter brown color for its lower beetroot extract concentration, indicating under-qualification as dental plaque staining materials. Therefore, 3% concentration (F2) has the best formulation regarding physical properties and stability. Conclusion: Formulas F1 and F2 have the best physical properties and stability by passing all the tests, while Formula 3 failed the organoleptic and flow rate tests.